Efeitos da atrazina na composição química e morfologia de cascas de ovos de Podocnemis Expansa (testudines, podocnemididae) incubados artificialmente - Souza, Rogério Rodrigues de (2013)
Egg shells serve as an indicator to investigate the effects of substances released into the environment. However, information about the impact of environmental contaminants on wildlife is scarce. It objected to study the chemical composition and morphology of egg shells of P. expansa over a period of artificial incubation and verify if the exposure to atrazine at zero day incubation interferes in the changes that occur in the eggshells. It used 168 eggs of P. expansa, that were artificially incubated and divided into four groups, according to exposure of eggs to the herbicide atrazine in four different concentrations: 0, 2, 20 and 200 ppb. The shells of eggs from all groups were analyzed in three periods: 1- 20, 21- 40 and 41- 60 days of incubation. Aspects of the chemical composition and morphology of the eggs were analyzed. There were significant differences in the chemical variables ether extract, crude protein and the real composition, and nitrogen and morphologically in thickness egg shells from P. expansa according to exposure to different concentrations of atrazine, particularly in incubation time of 60 days. In the morphological analysis by light microscopy and scanning electron microscopy there were no differences found.